Effects of the Order of Physical Exercises on Body Composition, Physical Fitness, and Cardiometabolic Risk in Adolescents Participating in an Interdisciplinary Program Focusing on the Treatment of Obesity - Branco, Braulio Henrique Magnani; Valladares, Débora; de Oliveira, Fabiano Mendes; Carvalho, Isabelle Zanquetta; Marques, Déborah Cristina; Coelho, Andressa Alves; de Oliveira, Leonardo Pestillo; Bertolini, Sônia Maria Marques Gomes (Frontiers in Physiology, 2019)
The main objective of this study was to investigate the effects of the order of physical exercises on body composition, physical fitness, and cardiometabolic risk in adolescents participating in an interdisciplinary program focusing on the treatment of obesity. The final 12-week analyses involved 33 female adolescents who were split into two groups of concurrent training (CT): resistance plus aerobic training and aerobic plus resistance training, with equalization performed in all physical exercises. The only difference between the two groups was the order in which the exercises were performed. The results showed reductions in fat mass, body fat, and waist circumference, as well as increases in musculoskeletal mass and resting metabolic rate (p< 0.05) following the multiprofessional intervention period. However, no signiﬁcant differences were observed in regard to body mass, body mass index, neck circumference, or arm circumference (p> 0.05). Maximal isometric strength and maximal oxygen consumption showed signiﬁcant increases after the intervention period (p< 0.05). There were reductions in insulin, HOMA-IR, total cholesterol, triglycerides, and low-density lipoproteins (p< 0.05), and an interaction within the resistance plus aerobic training group showed lower values for triglycerides when compared to itself (p= 0.002). No difference was found in fasting glycemia for either group (p> 0.05). It is worth noting that the equalization training variables presented no differences between the two groups (p> 0.05). Based on these results, both CT methods were found to be effective in promoting health parameters in overweight and obese female adolescents, and triglyceride values decreased more in the resistance plus aerobic group. Future studies with larger samples and feeding control should be conducted to confirm or refute our findings.